Socialization of Mount Merapi Disaster Management at Muhammadiyah Vocational School Cangkringan Yogyakarta - Raditya Argananta Churyanto; Tasya Noorhaliza; Iswanto Suwarno; Robbi Rahim; Nia Maharani Raharja (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Geographically, Argomulyo Village is near an active volcano, namely Mount Merapi. With these geographical conditions, the possibility of natural disasters occurring is very possible, starting from volcanic natural disasters and cold lava floods in the area. With the frequent occurrence of disasters, it is necessary to increase preparedness in dealing with disasters in the Argpmulyo Village community, so it is very necessary to carry out outreach to provide insight and knowledge to the community. The method used is conducting direct outreach in the school hall and simulations in the field. The target for this disaster response socialization activity is students of Muhammadiyah Cangkringan Vocational School. To improve disaster response and be smart in absorbing information for vocational school students as an initial step. The aim of this activity is for the community to have knowledge regarding disaster management and always be prepared when a disaster occurs at any time, so that they can create a strong personality and respond to disasters.